2007
DOI: 10.1590/s1517-83822007000300029
|View full text |Cite
|
Sign up to set email alerts
|

Formation of biofilms by Staphylococcus aureus on stainless steel and glass surfaces and its resistance to some selected chemical sanitizers

Abstract: The objectives of this work were to verify the capability of Staphylococcus aureus of forming bio-film on stainless steel and glass surfaces; to evaluate the efficiency of sodium dichloroisocyanurate, hydrogen peroxide and peracetic acid in inactivating Staphylococcus aureus cells adhered onto these surfaces; and to visualize biofilm development by scanning electron microscopy before and after sanitizer treatment. The surfaces studied consisted of 10x20mm chips immersed in Petri dishes containing BHI broth ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
112
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 13 publications
10
112
0
8
Order By: Relevance
“…Biofilms permit bacteria to persist in the environment and resist treatment with antibacterial agents, rendering their elimination very problematic (2)(3)(4). Bacteria, apart from the biofilm layer, can be a source of contamination and damage food quality, causing products to become the potential carriers of pathogens (5). Furthermore, it has been demonstrated that certain diseases such as periodontitis, cystic fibrosis, otitis media, native valve endocarditis, and chronic prostatitis all seem to be associated with biofilm-associated microorganisms (6).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms permit bacteria to persist in the environment and resist treatment with antibacterial agents, rendering their elimination very problematic (2)(3)(4). Bacteria, apart from the biofilm layer, can be a source of contamination and damage food quality, causing products to become the potential carriers of pathogens (5). Furthermore, it has been demonstrated that certain diseases such as periodontitis, cystic fibrosis, otitis media, native valve endocarditis, and chronic prostatitis all seem to be associated with biofilm-associated microorganisms (6).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in the present study for PAA confirm its effectiveness as a disinfectant, corroborating the results of other studies. 6,11,12,14,19 Marques et al demonstrated the high efficiency of PAA, but their results showed that S. aureus adhered to glass and stainless steel were not completely removed. 19 It is important to highlight that the authors applied PAA for 30 seconds and not for 10 minutes that is recommended by the fabricant for disinfection procedure.…”
Section: Discussionmentioning
confidence: 99%
“…6,11,12,14,19 Marques et al demonstrated the high efficiency of PAA, but their results showed that S. aureus adhered to glass and stainless steel were not completely removed. 19 It is important to highlight that the authors applied PAA for 30 seconds and not for 10 minutes that is recommended by the fabricant for disinfection procedure. 19 Even though no statistically significant difference was observed between the three disinfectants tested, contamination by S. aureus was observed in two pliers after treatment with 70% isopropyl alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…presentes no biofilme consolidado apresentaram uma forte resistência, sendo que células viáveis foram recuperadas após 24 horas de exposição aos desinfetantes analisados. Segundo Marques et al (2007), S. aureus na forma de biofilme se torna mais resistente aos agentes sanificantes. Esta resistência está associada tanto à baixa penetração dos compostos antimicrobianos no biofilme, como pelo estado fenotipicamente protegido, induzido nas bactérias que o compõe (Costerton et al 1995, Altieri et al 2013.…”
Section: Discussionunclassified